The Effect of Accounting Information System on Lending Policies - Gunanta, Remon; Hadian, Niki; Raiza Marwata, Sofa; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the paper is to evaluate the impact of the accounting information system on lending policies in Program Kemitraan Witel Bandung. The independent variable in this study is the accounting information system, and the dependent variable is lending policies. The research method used in this research is the descriptive verification research method. The results were analysed using simple linear regression analysis. The results showed that the accounting information system has a significant effect on lending policies.